Just add women and stir?: Education, gender and peacebuilding in Uganda. (March 2018) - Datzberger, Simone; Le Mat, Marielle L.J.
Highlights: Gender parity in education does not necessarily increase women's agency. Pragmatic understandings of gender limit education's potential for social transformation. A socio-historical informed gender analysis is absent from school curricula. The potential of education to re-negotiate gendered identities is overlooked. Abstract: Although Uganda is not short of policies and strategies to promote gender equality, women's political and social agency remains significantly low. Reasons are rooted in two main challenges: persisting structural barriers; and low levels of education among women. Both are most prevalent in the country's conflict-affected sub-regions. Against this backdrop, we explore and critically reflect on the interplay of education, gender and peacebuilding. We showcase how gender-responsive approaches in education at the macro-level have traditionally been based on initiatives that embrace gender equality by means of a "just add women and stir approach" thereby side-lining history, cultural sensitivity and context.